Names, Proverbs, Riddles, and Material Text in Robert Frost - O'Brien, T. author. aut Link
X, 210 p.
Keywords: This study examines several unexplored aspects of the poetry of Robert Frost, one of the most widely read and studied American poets, and shows how they contribute to the reader's experience and modernism in general.